Problematika Pendidikan Agama Islam pada Anak TNI di Komplek Asrama Widuri Medan - Ayu Lestari; Humaidah Br Hasibuan (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
Islamic Religious Education is an effort to convey and teach Islamic teachings to individuals so they can understand and practice the values, principles, and religious practices in their daily lives. This research aims to understand the implementation of Islamic Religious Education for the children of military personnel and the challenges parents face in providing this education. Additionally, this study seeks to identify the efforts that can be made to address these challenges. The method used in this research is qualitative, with data obtained through observation, interviews, and documentation. The results of the study indicate that there are several problems that hinder the implementation of Islamic Religious Education for the children of military personnel. These problems include the lack of time parents have due to their duties and the challenges of instilling religious values in a less supportive environment. Efforts to overcome these challenges include providing additional religious education outside the home, educating with an appropriate educational approach, and monitoring the daily activities of the children to ensure they receive adequate religious guidance.